P116 GIANT LEFT ATRIAL MYXOMA CAUSING ACUTE ISCHEMIC STROKE. (18th May 2022) - Chiarello, G; Garzya, M; Donateo, M; Marazia, S; Cucurachi, M; De Giorgi, A; Colonna, G
Abstract: Aims: Primary cardiac tumours are rare; most are benign, and around half are myxomas, often located in the left atrium. Clinical presentation is variable. Ischaemic stroke is a rare, although real and potentially fatal, complications of cardiac myxomas. Case Report: We present a case of a 51–year–old man, ex– smoker, obese, with history of hypertension and COPD, presented to our emergency department with right–sided hemiplegia and aphasia caused by ischaemic stroke. Brain CT revealed cerebral perfusion deficit. The patient was underwent intravenous thrombolytic strategy. TTE showed a large left atrial mass attached to the interatrial septum, with a friable appearance, suggestive of myxoma. The 2D and 3D TEE detected a giant space–occupying mass in the left atrium, coral–like, and the most apical portion prolapsed into the left ventricle during diastole, causing fixed obstruction to flow in the left ventricular inflow tract. In view of the risk of imminent embolization, the emergent surgical excision of the tumour was performed. Subsequent histopathological findings confirmed the diagnosis of myxoma. Symptomatic cardiac myxoma may present with one of the three classic clinical presentations of the Goodwin's triad, which include intracardiac obstruction, constitutional symptoms, and embolism. The obstructive pattern mimics atrioventricular valve obstruction. Constitutional manifestations include fatigue, fever, weight loss. Systemic embolization from myxoma occurs in around a third of cases. Of these, the most serious is cerebrovascular embolism, which may result in cerebral stroke. The tumour size, location, and macroscopic appearance, along with mean platelet volume and platelet count, are closely associated with embolic events. Echocardiography remains the method of choice for diagnosis and morphological characterization of myxoma. Two patterns have been established by echocardiography: round, with a solid appearance and a firm surface, and polypoid, with an irregular outline and a friable surface. The incidence of systemic embolization is higher in those with an irregular and friable surface and those that prolapse into the ventricle. Once a diagnosis of myxoma is established, surgical resection is the only effective treatment and should be performed immediately, in view of the risk of embolization. Conclusions: With this case report, we stress the importance of echocardiography in new onset of neurological deficit to prevent potentially fatal outcomes.